Review of the Problems and Legal Protection for Parties in the Implementation of Authentic Deeds Made Based on the Cyber Notary Concept in Indonesia - Sudarwati, Dini Anggraini; Mulia, Hansel Randy; Liesmawati, Liesmawati; Setiawan, I Ketut Oka (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
In the ever-evolving digital era, information technology has had a significant impact on various aspects of life, including in the fields of law and notary. One of the important innovations that has emerged is the concept of cyber notary, which uses digital technology in making authentic deeds, replacing conventional methods. It is hoped that cyber notary can increase efficiency, transparency, and accessibility in notary services, as well as reduce bureaucracy that often takes time and costs. However, the implementation of the cyber notary concept in Indonesia faces various complex problems. One of the main issues is the legal validity of deeds made digitally, including the recognition of electronic signatures and the process of authenticating the identities of the parties. In addition, data security and privacy protection are challenges in ensuring that information stored and transmitted digitally is not misused or hacked. On the other hand, the current regulations do not fully accommodate cyber notary practices. Legal gaps and unclear regulations create uncertainty for notaries and the parties who use their services. This reinforces the urgency to examine more deeply the need for comprehensive and adaptive legal updates to technological developments. This study focuses on the analysis of the problems in the implementation of authentic deeds based on cyber notary and legal protection for the parties involved. With a normative legal approach, this study aims to identify the main challenges and provide recommendations for policy makers and legal practitioners to improve the existing legal framework. It is hoped that the solutions found can support digital transformation in the notary sector in Indonesia, creating a more efficient, secure, and reliable system.